1999
DOI: 10.1038/15690
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment of apoptotic cells involves the redistribution of membrane phosphatidylserine on phagocyte and prey

Abstract: he clearance of cells that are dying by apoptosis is essential to the control of tissue homeostasis 1 . In contrast to classical models of phagocytosis, the molecular dissection of engulfment of apoptotic cells is still preliminary 1 . Genetic approaches in Caenorhabditis elegans have yielded several mutants, characterized by the persistence of apoptotic corpses 2-5 . In mammals, in vitro studies have mostly shed light on the macrophage receptors engaged in the recognition of apoptotic surfaces 1,6 . Both of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 18 publications
12
116
1
Order By: Relevance
“…6 Furthermore, it was demonstrated that redistribution of PS both on phagocyte and prey is involved in the engulfment of apoptotic cells. 7 This paper confirmed the inhibition by annexin V of apoptotic cell uptake. 7 In addition, annexin V was shown to decelerate apoptosis in CEM cells by its Ca 2+ channel activity.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…6 Furthermore, it was demonstrated that redistribution of PS both on phagocyte and prey is involved in the engulfment of apoptotic cells. 7 This paper confirmed the inhibition by annexin V of apoptotic cell uptake. 7 In addition, annexin V was shown to decelerate apoptosis in CEM cells by its Ca 2+ channel activity.…”
Section: Introductionsupporting
confidence: 73%
“…7 This paper confirmed the inhibition by annexin V of apoptotic cell uptake. 7 In addition, annexin V was shown to decelerate apoptosis in CEM cells by its Ca 2+ channel activity. 8 Usually engulfment of apoptotic cells induces neither inflammation 5 nor an immune response.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Neutrophils stimulated with chemotactic peptides, such as formylated Met-Leu-Phe (fMLP), exhibit transient cell surface PS expression [10]. Macrophages per se undergo membrane PS flip during their recognition and phagocytosis of dead cells [11][12][13][14]. Similarly, rapid changes in cell surface PS triggered by the natively expressed P2X7R in various leukocyte types have been associated with physiological signal transduction.…”
Section: P2x7r-mediated Regulation Of Plasma Membrane Composition Andmentioning
confidence: 99%
“…6 Furthermore, ABC1 was shown to be involved in engulfment of apoptotic cells. 7,8 One of the physiological roles of ABC transporters is detoxification by extrusion of various toxic compounds from the cytoplasm. [9][10][11] Detoxification is particularly crucial when cell injury occurs.…”
Section: Introductionmentioning
confidence: 99%